Determinación de la oferta hídrica de la concesión para la conservación el breo al río Huayabamba, centro poblado 2 de Mayo, provincia de Mariscal Cáceres - García Tello, Víctor Alfredo (2016)
The deterioration of water quality is a serious environmental, social and economic problem. Each liter of contaminated water that is poured means the loss of 100 liters of drinking water. The present work pursued as general objective to determine the quantity and quality of water that supply the conservation concession for the Huayabamba river Breo, populated center 2 Mayo, in the ofMariscal Caceres province. The study area corresponds to a territorial space in the area of influence of the conservation concession for the Breo, whose plant cover is without human intervention, therefore the importance of the study is to demonstrate that the conservation of forests contri bu tes water in quantity and quality for human consumption, overcoming in quantity and quality to the areas already intervened by anthropic activities, accordingly the study area is constituted by 08 monitoring stations located in Y ansanache, The Breo, Sulache and Cordoncillo River Streams, the first three are located in the interior of the conservation concession for the Breo-CCEB and the Cordoncillo River is located in the limit of the concession, Of the 08 selected sampling points has been evaluated physical chemical and microbiological parameters as Temperature, pH, Biochemical Oxygen Demand, Dissolved Oxygen, nitrates, phosphates. Turbidity, total solids dissolved and fecal coliforms. The parameters that have values that exceed the established standard in the D.S No. 015- 2015-MINAM, are the pH in Breo gully, reporting a value of6.05, whose value is below the established 6.5 to 8.5 pH units. Also the parameter that exceeds the standard is the sulfate in the sample point No. 8 ( Gelache river- Huayabamba river). In general surface water sources that are located on the inside of the conservation concession for the Breo presented a suitable quality for the conservation of the aquatic environment according to what is established in the Decree N° 015-2015-MINAM (Environmental Quality Standards for water- RCTS).